2016
DOI: 10.1080/2162402x.2016.1232222
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of myeloid cells by activated T cells determines the efficacy of PD-1 blockade

Abstract: Removal of immuno-suppression has been reported to enhance antitumor immunity primed by checkpoint inhibitors. Although PD-1 blockade failed to control tumor growth in a transgenic murine neuroblastoma model, concurrent inhibition of colony stimulating factor 1 receptor (CSF-1R) by BLZ945 reprogrammed suppressive myeloid cells and significantly enhanced therapeutic effects. Microarray analysis of tumor tissues identified a significant increase of T-cell infiltration guided by myeloid cell-derived chemokines CX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 53 publications
0
37
0
Order By: Relevance
“…Mao et al reported that targeting of CSF-1Rþ+ suppressive myeloid cells in combination with CPis caused spontaneous control of NBL in vivo [42], a mechanism confirmed in several other types of cancers, as reviewed by Weber et al [115]. A possible explanation for this is the observation that T cells start to produce M-CSF upon PD-1 blockade, which can bind to CSF-1R on myeloid-derived suppressor cells, thereby enhancing their suppressive phenotype [116]. This causes a further reduction of IFN-regulated chemokine release (e.g., CXCL9, 10, and 11) in the TME, which are important for T cell infiltration and could therefore potentially explain the synergistic effect of targeting CSF-1Rþ+ suppressive myeloid cells in combination with CPi.…”
Section: Checkpoint Inhibitorsmentioning
confidence: 89%
“…Mao et al reported that targeting of CSF-1Rþ+ suppressive myeloid cells in combination with CPis caused spontaneous control of NBL in vivo [42], a mechanism confirmed in several other types of cancers, as reviewed by Weber et al [115]. A possible explanation for this is the observation that T cells start to produce M-CSF upon PD-1 blockade, which can bind to CSF-1R on myeloid-derived suppressor cells, thereby enhancing their suppressive phenotype [116]. This causes a further reduction of IFN-regulated chemokine release (e.g., CXCL9, 10, and 11) in the TME, which are important for T cell infiltration and could therefore potentially explain the synergistic effect of targeting CSF-1Rþ+ suppressive myeloid cells in combination with CPi.…”
Section: Checkpoint Inhibitorsmentioning
confidence: 89%
“…Nonetheless, given the expression of numerous checkpoint receptors on T cells, antitumor efficacy of the combination of CD40 agonism and CSF-1R blockade may be further improved by including checkpoint blockade. Checkpoint blockade has complemented TAM-directed therapies in various tumor models (48)(49)(50), and future experiments will investigate whether including anti-PD-1 checkpoint blockade in combination with anti-CD40/anti-CSF-1R combination therapy will provide additional benefits. The present studies demonstrated the advantage of combining CD40 agonism with CSF-1R blockade to produce the most effective tumor control and extend survival.…”
Section: Foxp3mentioning
confidence: 99%
“…As the expression of PD‐L1 on antigen‐presenting cells is indispensable for the induction of inducible (i)Tregs, PD‐L1 enhances and sustains Foxp3 expression and the suppressive function of iTregs, and CCL22 plays a role in recruitment of Tregs in the tumor site, the suppression of PD‐L1 and CCL22 by DTIC is important to evaluate their antitumor effects for melanoma‐bearing hosts. Although it was not possible to detect CXCL9, CXCL10 and CXCL11 in the present system, the antitumor effects of these chemokines are still controversial . Th1 chemokines recruit effector T cells in the tumor site, but their role in tumor progression differs between tumor types .…”
Section: Discussionmentioning
confidence: 83%